BTLA blockade enhances Cancer therapy by inhibiting IL-6/IL-10-induced CD19high B lymphocytes. Issue 1 (21st November 2019) - Chen, Yu-Li; Lin, Han-Wei; Chien, Chung-Liang; Lai, Yen-Ling; Sun, Wei-Zen; Chen, Chi-An; Cheng, Wen-Fang
Abstract : Background: The standard treatment for epithelial ovarian carcinoma (EOC) is surgery followed by platinum/paclitaxel-based chemotherapy, but the overall survival rate is poor. The purpose of this study was to investigate the therapeutic potential of chemotherapy combined with inhibition of B and T lymphocyte attenuator (BTLA) for clinical use to treat EOC. Methods: Initially, we evaluated the potential application of chemotherapy combined with anti-BTLA antibody in an animal model. We then analyzed the distribution and regulation of BTLA expression on immunocytes in vitro. Finally, we examined the correlation between BTLA expression levels in cancerous tissues and prognosis in 254 EOC cases. Results: The combination of chemotherapy and anti-BTLA antibody for inhibiting BTLA significantly reduced peritoneal tumor volume and extended survival in tumor-bearing mice. In addition, BTLA could be identified mostly on B lymphocytes, especially on CD19 hi B cells, rather than on T lymphocytes and natural killer cells. Under regulation of interleukins 6 and 10, more BTLA + CD19 hi B lymphocytes could be induced through AKT and STAT3 signaling pathways. Detectable BTLA expression in ovarian cancerous tissues was associated with worse disease-free and overall survivals of EOC patients. Conclusions: BTLA detected in cancerous tissues can predict poor outcome of EOC patients. Inhibition of BTLA combined with chemotherapy can elevate immune activation and generate potent anti-tumor effects. Thus, the combination of chemotherapy and anti-BTLA antibody may hold potential clinical application for the treatment of EOC patients. Trial registration: The Trial Registration Number was NCT00854399 .